Effects of 10% carbamide peroxide bleaching materials on enamel microhardness - Rodrigues, J. A.; Basting, R. T.; Serra, Mônica da Costa [UNESP]; Rodrigues, A. L. (Mosher & Linder, Inc, 2001)
Purpose: To evaluate the microhardness of enamel treated with two different 10% carbamide peroxide bleaching materials at different time intervals. Materials and Methods: Two bleaching agents were analyzed: Opalescence (OPA) and Rembrandt (REM). The control group (CON) consisted of dental fragments maintained in artificial saliva. Bleaching was accomplished for 8 hrs per day and stored during the remaining time in an individual recipient with artificial saliva. Enamel microhardness testing was performed before the initial exposure to the treatments and after 1, 7, 14, 21, 28, 35 and 42 days. Results: the ANOVA, followed by the Bartlet and Tukey tests, showed significant differences for treatments (P < 0.00001) from day 7-day 42. From the 7th to the 14th day, OPA presented an increase of enamel microhardness over time while REM presented a decrease of microhardness. Statistical differences were not found between REM and the control group (OPA > CON = REM). From the 21st-35th day, enamel fragments bleached with OPA and REM presented a decrease of microhardness. Statistical differences of microhardness were verified among all the treatments (OPA > CON > REM). on the day 42, statistical differences were not found between OPA and the control group, but they were found between REM and the control group (OPA = CON > REM). The polynomial regression showed an increase of microhardness for OPA until the 21st day, followed by a decrease of microhardness up to the 42nd day. A decrease of microhardness for REM was verified. There were alterations in enamel microhardness as a function of bleaching time when using the two different 10% carbamide peroxide whiteners. Over a 42-day treatment time, bleaching with REM agent caused a decrease in enamel microhardness. The OPA agent initially increased the microhardness, then returned to the control level. Different bleaching materials with the same concentration of carbamide peroxide have different effects on the enamel.